1996
DOI: 10.1021/ja952317i
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 3-Dehydroshikimic Acid with Molecular Oxygen and Hydrogen Peroxide:  Products, Mechanism, and Associated Antioxidant Activity

Abstract: In the presence of molecular oxygen or hydrogen peroxide, inorganic phosphate catalyzes the conversion of 3-dehydroshikimic acid (DHS) into gallic acid. Other products formed in the reaction of DHS with oxygen include protocatechuic acid, tricarballylic acid, and pyrogallol. With hydrogen peroxide as oxidant, pyrogallol formation is not observed, and smaller amounts of tricarballylic acid are produced. Evidence favoring a mechanism involving phosphate-catalyzed tautomerization of DHS to a reactive enediol inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…HR-FAB-MS of 5 displayed a molecular ion at m/z 305.2844 and indicated its molecular formula as C 21 C-NMR of the molecule showed the presence of 21 C-atoms in the molecule, and the DEPT spectrum helped to assign them to six CH, six CH 2 , and six Me groups, and three quaternary C-atoms. The DEPT spectrum also confirmed that one of the Me groups belonged to a MeO moiety.…”
mentioning
confidence: 99%
“…HR-FAB-MS of 5 displayed a molecular ion at m/z 305.2844 and indicated its molecular formula as C 21 C-NMR of the molecule showed the presence of 21 C-atoms in the molecule, and the DEPT spectrum helped to assign them to six CH, six CH 2 , and six Me groups, and three quaternary C-atoms. The DEPT spectrum also confirmed that one of the Me groups belonged to a MeO moiety.…”
mentioning
confidence: 99%
“…3). An accurate analysis of 1 H NMR spectra showed weak signals in the aromatic region, attributable to the aromatic compounds previously found by Frost [9] (as seen by NMR, by adding small amounts of standard reference compounds), likely the by-products that are responsible for the reduced selectivity. An accurate analysis of the [a] D of the DHS produced always gave the expected value reported in the literature [15], thus ruling out the indirect involvement of racemization of the chiral centres of shikimic acid in the chemical transformation.…”
mentioning
confidence: 74%
“…Among these, McKittrick and Ganem [8] reported 65% yields for DHS using THF as the solvent and an excess (3:1) of the exotic oxidant dichlorodicyanobenzoquinone. Another important aspect to be considered is the extreme lability of DHS under even mild oxidation conditions: water solutions of DHS in the presence of 1 M phosphate buffer at pH 6.7 and at 40°C under aerobic conditions result in its almost quantitative aromatisation to gallic and protocatechuic acid, and its decarboxylation to pyrogallol [9]. The large use of DHS makes it necessary to search for a low cost (and 'greener') chemical pathway for its synthesis.…”
mentioning
confidence: 99%
“…Production of DHS was associated with the formation of dehydroquinate and gallic acid, which could be products of abiotic conversion reactions (Richman et al, 1996). Gallic acid production could also be due to formation of protocatechuic acid by DHS dehydratase, followed by a hydroxylation step .…”
Section: -Dehydroshikimic Acid Productionmentioning
confidence: 99%